WiDom: a dominance protocol for wireless medium access - Pereira, Nuno (2014)
In this paper, we address the problem of sharing a wireless channel among a set of sporadic message streams where a message stream issues transmission requests with real-time deadlines. We propose a collision-free wireless medium access control (MAC) protocol which implements static-priority scheduling, supports a large number of priority levels and is fully distributed. It is an adaptation to a wireless channel of the dominance protocol used in the CAN bus. But, unlike that protocol, our protocol does not require a node having the ability to receive an incoming bit from the channel while transmitting to the channel. The evaluation of the protocol with real embedded computing platforms is presented to show that the proposed protocol is in fact collision-free and prioritized. We measure the response times of our implementation and show that the response-time analysis developed for the protocol offers an upper bound on the response times.